2018
DOI: 10.18203/2319-2003.ijbcp20185165
|View full text |Cite
|
Sign up to set email alerts
|

A study on the prescription pattern of antifungal drugs in the Dermatology Department of a tertiary care teaching hospital in Southern Kerala

Abstract: Background: Skin disorders form 2% of total Out Patient Department consultations worldwide. But no such data is available from India. Studying prescription pattern is a component of medical audit that help prescribers to provide rational and cost-effective medical care. This study is about the prescription pattern of antifungals in this institution and will help in developing local policies for appropriate use of antifungal drugs. The objective was to study the prescription pattern of antifungals in dermatolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 2 publications
2
8
0
Order By: Relevance
“…12 Gopimohan et al study showed average 3.12 drugs per encounter were prescribed. 15 Patil et al study showed average number of drugs per prescription was 3.27. 8 This is similar to current study, but according to WHO the average number of drugs per encounter was 5.13.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Gopimohan et al study showed average 3.12 drugs per encounter were prescribed. 15 Patil et al study showed average number of drugs per prescription was 3.27. 8 This is similar to current study, but according to WHO the average number of drugs per encounter was 5.13.…”
Section: Discussionmentioning
confidence: 99%
“…Gopimohan et al study showed that average number of antifungal prescribed per encounter was 2. 15 Average number of systemic and topical antifungal drugs prescribed per encounter were 1 and 1.10 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, haematology‐oncology units contributed to maximum antifungal use in our hospital. A few population‐specific studies from India reported antifungal use of 3.28%–41.2% in the ICUs, 6.16% in febrile neutropenia patients, 7.6%–16% in an oncology hospital and 33.33% in a dermatology OPD 31‐35 . The low antifungal use in our study could be due to the comparatively better awareness of fungal diseases and the availability of reference mycology laboratory in this tertiary care centre.…”
Section: Discussionmentioning
confidence: 55%
“…A few population-specific studies from India reported antifungal use of 3.28%-41.2% in the ICUs, 6.16% in febrile neutropenia patients, 7.6%-16% in an oncology hospital and 33.33% in a dermatology OPD. [31][32][33][34][35] The low antifungal use in our study could be due to the comparatively better awareness of fungal diseases and the availability of reference mycology laboratory in this tertiary care centre. However, 50% of Asian tertiary care centres do not have equipped mycology laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…18 In Gopimohan et al most commonly prescribed topical agent was terbinafine. 19 Antifungal soaps and powders were also prescribed along with oral and topical antifungal drugs in few prescriptions. Out of 2331 antifungal drugs, prescribed 331 antifungal drugs were soaps and powders.…”
Section: Discussionmentioning
confidence: 99%